Effect of HIV-exposure and timing of antiretroviral treatment initiation in children living with HIV on antibody persistence and memory responses to Haemophilus influenzae type b and pneumococcal polysaccharide-protein conjugate vaccines. Issue 12 (10th March 2020) - Madhi, Shabir A.; Izu, Alane; Violari, Avy; Cotton, Mark F.; Jean-Philippe, Patrick; Otwombe, Kennedy; Adrian, Peter V.; ,
Highlights: Early initiation of ART in children with HIV results in good memory responses to PCV and HibCV. HIV-exposed, uninfected children mount good memory responses to PCV and HibCV immunization. PCV and HibCV are likely to be effective in protecting against invasive disease in children with HIV on ART. Abstract: Background: We investigated the effect of in utero HIV-exposure, timing of antiretroviral treatment (ART) initiation, and ART interruption on memory responses and persistence of immunity induced by pneumococcal (PCV) and Haemophilus influenzae type b (HibCV) polysaccharide-protein conjugate vaccines. Methods: Children were enrolled (6–12 weeks of age), and vaccinated with a three-dose primary series of 7-valent PCV (PCV7) and HibCV at 6, 10 and 14 weeks of age. Study groups included infants infected with HIV perinatally with CD4+ ≥ 25% initiating ART following immunological or clinical deterioration (ART-Def), or immediately upon enrolment followed by interruption at 40 (ART-Immed/40w) or 96 weeks (ART-Immed/96w); and HIV-uninfected infants with (HEU), and without HIV (HIV-unexpsoed) exposure in utero. Within each group, children were randomized to receive either a booster dose of PCV7 or HibCV at 15 months of age. PCV serotype-specific and polyribosyl ribitol phosphate (PRP) IgG were measured pre-boost, two-weeks post-boost and at two-years of age. Opsonophagocytic activity (OPA) to serotypes 9V, 19F and 23F was measured post-booster dose. Results: Persistence of IgG to PCV vaccine–serotypes and anti-PRP was similar in all groups of children living with HIV (CLWH) compared to HIV-unexposed children. Anamnestic responses to PCV and HibCV were also similar in all three groups of CLWH compared to HIV-unexposed children. CLWH, however, tended to have lower functional antibody (OPA) titers than HIV-unexposed children after the PCV booster dose for some serotypes. Immunity to PCV and HibCV was similar between the ART-Immed/40w and ART-Immed-96w groups. There were no differences in IgG kinetics between HEU and HIV-unexposed children. Conclusions: A three dose primary series, with or without PCV or HibCV booster doses in CLWH initiated on ART during infancy, would likely be similarly effective in preventing invasive bacterial disease as in HIV-unexposed children.